The Badly Behaved Production Function: Comment - Bruno, Michael; Burmeister, Edwin; Sheshinski, Eytan (Quarterly Journal of Economics, 1968)
Michael Bruno, Edwin Burmeister, Eytan Sheshinski; The Badly Behaved Production Function: Comment, The Quarterly Journal of Economics, Volume 82, Issue 3,